Rhizopus Species from Fresh Tempeh Collected from Several Regions in Indonesia - Anastasia Tatik Hartanti; Gayuh Rahayu; Iman Hidayat (Bogor Agricultural University, Indonesia, 2015)
Recent changes in taxonomy of Rhizopus, which are now heavily relying on molecular approach, create significant problem in assigning species name to particular Rhizopus strains isolated from various sources, including tempeh. The present study aims to determine 36 strains of Rhizopus from tempeh originated from 26 locations in Indonesia, using combination of molecular phylogenetic analysis based on internal transcribed spacer ribosomal DNA sequence, physiology, and morphology to species level. The results showed that most of the strains belong to R. microsporusecomplex, and only one strain belongs to R. delemar. Morphological variations within R. microsporus were observed, but under current approach they were insufficient for infraspecific delimitation. The current report is an important contribution in validating the identity of Rhizopus from fresh tempeh in Indonesia.